Model Blended Learning dalam Meningkatkan Efektifitas Pembelajaran - Abdullah, Walib (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2018)
In the 21st century learning is already entered to the digital era , which is many educational practitioners have developed and designing a digital-based learning such as online learning. However Online learning still needs the other learning namely face-to-face learning. That is why Educational experts combine these two lessons mode into a new learning theory called by Blended Learning. Blended learning is a combination of online learning, offline learning, and face-to-face learning, because there are many researchs prove that blended learning has more influential rather than online learning or face-to-face leaarning in improving students’ learning intrest rather than online learning or face-to-face learning. Blended learning may apply by using these following combination namely 50/50, 75/25, or 25/75 from the learning period alocation. There are some cases need to be consideration in designing a blended learning, it is about how to make the learning is so interesting and suitable with the characteristic of students’ learning style.